JSON-based control model for SQL and NoSQL data conversion in hybrid cloud database - Zhang, Lei; Pang, Ke; Xu, Jiangtao; Niu, Bingxin (Journal of cloud computing : advances, systems and applications, 2022)
A data interaction transformation model, XYJSON, that is suitable for all data using current standard SQL syntax and JSON document data is proposed to solve the problem of increasing development workload and difficulty caused by using different control methods for corresponding types of databases under the cloud hybrid storage. A control program was studied to control relational and NoSQL data at the same time, by establishing a general conversion model between relational and NoSQL data and converting standard SQL statements into JSON. The performance of XYJSON was compared with that of the traditional mode. The results show that the performance difference between XYJSON and the traditional mode is small. In addition, a developer survey was conducted on XYJSON for user friendliness and compatibility. All developers rated XYJSON as excellent. The current cloud hybrid storage cannot use a unified control model to realize data control. XYJSON breaks through this bottleneck, making it easier and more efficient to control different types of databases under cloud hybrid storage.